2022
DOI: 10.1002/adsc.202200254
|View full text |Cite
|
Sign up to set email alerts
|

Selective 5‐Exo‐Dig versus 6‐Endo‐Dig Cyclization of Benzoimidazole Thiols with Propargyl Alcohols

Abstract: We describe here the Lewis acid‐promoted cyclization reaction of benzomidazole thiols with propargyl alcohols for the selective synthesis of benzoimidazolo thiazines and benzothiazolo imidazoles. The reaction is regioselective and the solvent controls the formation of products. The systematic study to determine the best reaction conditions revealed that the six‐membered benzoimidazolo thiazines were obtained by reacting the benzoimidazole thiols with propargyl alcohols in the presence of boron trifluoride ethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
(81 reference statements)
0
2
0
Order By: Relevance
“…Hao et al 10 described a onepot tandem reaction to efficiently synthesize 1,4-benzoxazine derivatives without the need for transition metal catalysts, under mild conditions (Figure 1b). In a recent innovation, Goulart et al 11 explored the BF 3 •OEt 2 -catalyzed reaction between propargyl alcohol and benzimidazole thiol in different solvent (Figure 1c). They found that using DCM solvent primarily yields the six-membered benzimidazole thiazine via 6-endo-dig cyclization, while switching to DMF solvent results in the formation of five-membered benzothiazole imidazole through 5-exo-dig cyclization.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hao et al 10 described a onepot tandem reaction to efficiently synthesize 1,4-benzoxazine derivatives without the need for transition metal catalysts, under mild conditions (Figure 1b). In a recent innovation, Goulart et al 11 explored the BF 3 •OEt 2 -catalyzed reaction between propargyl alcohol and benzimidazole thiol in different solvent (Figure 1c). They found that using DCM solvent primarily yields the six-membered benzimidazole thiazine via 6-endo-dig cyclization, while switching to DMF solvent results in the formation of five-membered benzothiazole imidazole through 5-exo-dig cyclization.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Prompted by our long-standing interest in organic reaction mechanisms, we undertook an investigating into the mechanisms and the origin of solvent-induced chemoselectivity of this reaction. Goulart et al 11 presented initial hypotheses on the cyclization mechanisms in the aforementioned two solvents (Scheme 1). In DCM, the reaction begins with propargyl alcohol 1a to form IM1, which then undergoes C−O bond cleavage to generate the propargyl cation IM2 and its allenic form IM2′.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Propargyl alcohols are ubiquitous building blocks in chemical synthesis, being highly valued for their widespread application as valuable synthetic intermediates or medicinally relevant molecules themselves. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] They participate in a diverse array of transformations, owing this to their multifunctionality, and thereby being the subject of numerous studies. Protected propargyl alcohols can be accessed via well-developed stoichiometric methods, including mainly the use of a combination of propargyl alcohol, chlorosilane and organolithium reagent (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Boron trifluoride etherate is a commonly employed reagent in organic synthesis due to its combination of powerful Lewis acidity and ease of handling. In contrast, the related sulfur analogue boron trifluoride dimethyl sulfide (BF 3 SMe 2 ) has received considerably less attention. Perhaps the most well-known and earliest reported use of this system is benzyl group cleavage using a combination of boron trifluoride etherate and dimethyl sulfide.…”
Section: Introductionmentioning
confidence: 99%